Sistem Pakar Diagnosa Penyakit Bawang Merah Menggunakan Metode Forward Chainning - Titi Supianti; Ahmad Ashril Rizal Ashril; Lalu Puji Indra Kharisma; Khairunnazri (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
Consulting someone who has expertise in a particular field in solving a problem is the right choice in order to get the best answer, solution, decision or conclusion. An expert's answer to a consultation is of course very trustworthy or accountable and can affect the quality and quality of the results of a solution to a problem, this is because an expert always masters the field he is engaged in based on his knowledge and experience.Likewise, shallot plant farmers who experience various problems or various factors including cultivation techniques, environmental conditions and pests and diseases. However, in determining the disease contained in this shallot plant, it is still using the manual method so it requires a more complicated and time-consuming process. An expert system is a computer system that emulates the decision-making ability of an expert. Based on these problems, an application that is able to analyze a disease in shallot plants is designed quickly and precisely with the title "Expert System for Diagnosis of Shallot Plant Diseases Using the Forward Chainning Method".